THE INFLUENCE OF HUMOR ADVERTISING, CONTENT MARKETING AND PSYCHOLOGICAL FACTORS ON BRAND AWARENESS IN SHOPEE’S YOUTUBE COMMERCIAL “SHOPEE COD (TUKUL ARWANA’S VERSION)” - Claudio Enrico Gabriel Bate; David P. E. Saerang; Regina T. Saerang (Universitas Sam Ratulangi, 2022)
The increasing of digital-based business, transforms traditional marketing into interactive marketing, where consumers can interact directly with brands. YouTube as one of the popular social media today also contributes to online advertising brand awareness. This study aims to analyze the Influence of Humor Advertising, Content Marketing, and Psychological Factors on YouTube Commercial towards Brand Awareness. The population in this study were students of Sam Ratulangi University. The sampling technique uses purposive sampling and obtained 100 respondents that were used as samples. Multiple regression analysis method is used to analyze the effect of the independent variable on the dependent variable. The results showed that partially Humor advertising had no effect on brand awareness while Content Marketing and Psychological Factors had a significant positive effect on brand awareness of YouTube Commercial. Simultaneously, Humor Advertising, Content Marketing, and Psychological Factors have a significant effect towards brand awareness on Youtube Commercial.